1994
DOI: 10.1016/0032-3861(94)90399-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformations of a liquid crystalline epoxy during curing

Abstract: The phase transformations of a novel liquid crystalline epoxy, digiycidyl ether of 4,4'-dihydroxy-~tmethylstilbene (DGEDHMS), from isotropic phase to liquid crystalline phase during curing have been studied using a cross-polarized optical microscope equipped with a hot-stage. Time-temperaturetransformation (TTT) diagrams were constructed following the isothermal curing of the DGEDHMS in the isotropic phase with a difunctional amine, the aniline adduct of the DGEDHMS, and a tetrafunctional sulfonamido amine, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 13 publications
2
34
0
Order By: Relevance
“…Ober et al reported the synthesis, curing behavior and anisotropic mechanical properties of stilbene epoxy resins [1][2][3][4][5]. Yee et al investigated the morphology of stilbene epoxy resin and the effect of curing reaction on liquid crystallinity [6] Carfagna et al observed the isothermal curing behavior and morphological change of stilbene epoxy resin [7]. Mallon et al studied LCE resins with aromatic ester unit in the main chain [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ober et al reported the synthesis, curing behavior and anisotropic mechanical properties of stilbene epoxy resins [1][2][3][4][5]. Yee et al investigated the morphology of stilbene epoxy resin and the effect of curing reaction on liquid crystallinity [6] Carfagna et al observed the isothermal curing behavior and morphological change of stilbene epoxy resin [7]. Mallon et al studied LCE resins with aromatic ester unit in the main chain [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among these materials liquid crystalline epoxy (LCE) resins have gained considerable interest due to their advantages like controllable curing rate, high heat and chemical resistance and high mechanical properties. Epoxy resins with aromatic stilbene structure were investigated by many research groups [1][2][3][4][5][6][7][8]. Ober et al reported the synthesis, curing behavior and anisotropic mechanical properties of stilbene epoxy resins [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of epoxy fact that the mesogenic epoxy resins lose their thermosets, new types of epoxy resins which conliquid crystallinity with the progress of curing tain the mesogenic groups in their backbone, such was also reported. 10,14 We have also investigated as biphenol-type, [1][2][3][4] stilbene-type, [5][6][7][8] phenylbenthe thermal and mechanical properties of an epzoate-type, [9][10][11][12] and azine-type 13 resins, have been oxy resin which includes the biphenol group as a reported of both theoretical and practical interest. mesogenic group.…”
Section: Introductionmentioning
confidence: 99%
“…LC epoxy thermosets contain rigid mesogenic groups in their backbone moiety of network chains, such as biphenyl, [9][10][11][12] stilbene, [13][14][15][16][17][18][19][20][21] azomethine, [22][23][24][25][26][27] ester, [28][29][30][31][32][33] azo, 34,35 and other, 36 which show excellent mechanical and thermal properties. LC epoxy thermosets contain rigid mesogenic groups in their backbone moiety of network chains, such as biphenyl, [9][10][11][12] stilbene, [13][14][15][16][17][18][19][20][21] azomethine, [22][23][24][25][26][27] ester, [28][29]…”
Section: Introductionmentioning
confidence: 99%